Wildland fire smoke exposure disparities by wildland urban interface category and land ownership - Jihoon Jung; Claire L. Schollaert; Yuta J. Masuda; Rachel E. Connolly; Eimy Bonilla; Kane Samuel; Daja Elum; Ryan D. Haugo; John T. Bandzuh; Bok Haeng Baek; Miriam E. Marlier; June T. Spector; et al. (Landscape and Urban Planning, 2025)

Tamm review: A meta-analysis of thinning, prescribed fire, and wildfire effects on subsequent wildfire severity in conifer dominated forests of the Western US - Kimberley T. Davis; Jamie Peeler; Joseph Fargione; Ryan D. Haugo; Kerry L. Metlen; Marcos D. Robles; Travis Woolley (Forest Ecology and Management, 2024)

Advancing the community health vulnerability index for wildland fire smoke exposure - Jihoon Jung; Joseph L. Wilkins; Claire L. Schollaert; Yuta J. Masuda; John C. Flunker; Rachel E. Connolly; Savannah M. D'Evelyn; Eimy Bonillia; Ana G. Rappold; Ryan D. Haugo; Miriam E. Marlier; June T. Spector (Science of The Total Environment, 2024)

Does large area burned mean a bad fire year? Comparing contemporary wildfire years to historical fire regimes informs the restoration task in fire-dependent forests - Daniel C. Donato; Joshua S. Halofsky; Derek J. Churchill; Ryan D. Haugo; C. Alina Cansler; Annie Smith; Brian J. Harvey (Forest Ecology and Management, 2023)

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Erratum to: Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)

Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)